Critique of the digital world: a categorization proposal - Codina, Lluís; Abadal, Ernest (Anuario ThinkEPI, 2013)
Web criticism in general and search engines criticism in particular have increased in parallel to the importance they gained over time. This paper proposes a categorization of these weaknesses of search engines and the web in order to provide a conceptual clarification. These shadow zones are classified into three levels: technological (issues that directly depend on the technology, whether the limitations in indexing, the list of results or relevance calculation), cognitive (the problems of access and interpretation of the contents by the user) and political (privacy, censorship and other matters affecting people's rights and freedom). In conclusion, we highlight the importance of transversal and interdisciplinary approaches to understand the full complexity of these questions.
Keywords: Web; Search engines; Web criticism; Search engine limitations; Weaknesses.